Reproductive phenology and fruit production on a land bridge island in the brazilian atlantic forest - Genini, Julieta [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
As florestas tropicais estão entre os ambientes mais produtivos do planeta, sendo que a quantidade de frutos kg/ha pode chegar a 180-1000 kg/ha. Apesar dessa alta produtividade, a fenologia é altamente sazonal, ocorrendo períodos de escassez de recursos e alta produtividade no mesmo ano e/ou entre anos. Os frugívoros exibem uma ampla variedade de adaptações comportamentais e ecológicas para superar esses períodos de escassez. O presente trabalho avaliou as variações temporais na disponibilidade de frutos consumidos por vertebrados frugívoros na Ilha Anchieta, São Paulo, Brasil. Nós procuramos responder às seguintes questões: Os padrões de frutificação e disponibilidade de frutos diferem entre arbóreas e palmeiras? e Os padrões fenológicos de frutificação diferem entre grupos de palmeiras com diferentes síndromes de dispersão?. Os padrões fenológicos foram sazonais para ambos os grupos, no entanto, as datas de ocorrência dos eventos de frutificação foram diferentes. A produção de frutos também foi diferente entre palmeiras e arbóreas, sendo que as palmeiras constituíram mais de 80 por cento do total da biomassa coletada. Os padrões fenológicos foram diferentes entre as palmeiras com diferentes sub-síndromes de dispersão (dispersas por roedores, mistas e aves) fornecendo recursos alimentares para diferentes grupos de frugívoros ao longo do ano. As palmeiras poderiam constituir um recurso alimentar alternativo em períodos de baixa disponibilidade de frutos embora não forneçam recursos para os diferentes tipos de frugívoros da Ilha Anchieta o ano todo.

Tropical rainforest is considered one of the world s most productive habitats where fruit biomass ranges between 180-1000 kg/ha/yr. Despite this broad fruit production, phenology is highly seasonal in tropical forests, showing alternate periods of fruit scarcity and high resource production both in the same year and/or between different years. Frugivores exhibit a variety of ecological and behavioral adaptations to overcome these fluctuations. We evaluate the temporal variation in the availability of fruits consumed by vertebrate frugivores on Anchieta Island, in the Brazilian Atlantic Forest, Northeast São Paulo State. We aim to answer the following questions: Do fruiting patterns and the availability of fruits consumed by vertebrate frugivores differ between palms and trees? Do palm fruiting patterns differ among seed dispersed groups (rodent, mixed and bird)? Phenological patterns were seasonal for both trees and palms; however, the times of occurrence of fruiting differed. Fruit fall biomass was also different between trees and palms, and palms constituted more than 80 percent of the overall fruit fall biomass. Phenological patterns differed between the seed dispersed palms groups (rodent, mixed and bird seed dispersed palms) providing food resources in distinct periods for different assemblages of vertebrate frugivores. Palms may constitute an alternative food resource in periods of low fruit availability, although they do not provide resources for the entire assemblage of vertebrate frugivores on Anchieta Island all year.
Keywords: Botânica; Fenologia; Palmeira; Fruits; Phenology; Palms; Seasonality; Frugivores